Post-acute college student satisfaction with telepsychiatry during the COVID-19 pandemic. (July 2022) - Michaels, Timothy I.; Singal, Sonali; Marcy, Patricia; Hauser, Marta; Braider, Laura; Guinart, Daniel; Kane, John M.
Abstract: Objectives: Patient satisfaction with telepsychiatry during the COVID-19 pandemic has generally been positive, but few studies have compared patient experiences across settings, and no study to date has investigated the experience of college students receiving post-acute mental health treatment in an outpatient setting. Participants: The current study surveyed college student outpatients (n = 101) to understand their experiences using telehealth during the COVID-19 pandemic. Methods: An anonymous survey was delivered electronically and included questions regarding patients' age, treatment length, telehealth use, and their experience and satisfaction with telepsychiatry. A mixed-methods approach was used to analyze responses between groups through Chi-Square, Kruskal-Wallis, or Mann-Whitney tests, and qualitatively to understand themes across items related to the benefits and challenges of telehealth. Results: College students were more likely to utilize video-based telehealth and preferred video-based care. College students receiving medication management were much more likely to endorse telehealth being as helpful as in-person treatment. Several challenges associated with telehealth were raised in both groups. Conclusions: Understanding the benefits and challenges of telepsychiatry in this high-risk college population may help enhance access to care during a critical period of development in which most psychopathology emerges.